Search 83,569 tutors
FIND TUTORS
Ask a question
0 0

solve for x when 4(x+3)=3[x-(2-x)]

Tutors, please sign in to answer this question.

2 Answers

4x + 12 = 3x - 6 + 3x
4x + 12 = 6x - 6   (add the 3x's together)
12 = 2x - 6  (subtract 4x from both sides of equation)
18 = 2x  (add 6 to both sides of equation)
9 = x  (divide each side of equation by 2)
 
 
 
Distribute first:
4x + 12 = 3[x - 2 + x]
                        (make sure to distribute the negative, making the 2 negative and the x positive)
Continue distributing on the right:
4x + 12 = 3x - 6 + 3x
Combine like terms:
4x + 12 = 6x - 6
Now put all like terms together on same side:
4x-6x = -6 - 12 (subtract 6x and 12 from both sides)
Combine like terms:
-2x = -18 (same sign, add together and keep the sign)
Divide both sides by -2 to isolate x:
x = 9